Derecho de seguros y derecho del consumidor: diálogo de fuentes a la luz de la jurisprudencia - Vázquez Ferreyra, Roberto A. (2022)
Fil: Vázquez Ferreyra, Roberto A. Universidad Nacional de Rosario; Argentina